The Characteristic Study on the Extraction of a Co Ion in the Metal Ion Implanter - Trịnh, Thị Tú Anh (2023)
Proton Engineering Frontier Project (PEFP) has supplied the metal ions to users by using an installed metal ion implanter of 120 keV. At present a feasibility study is being performed for a cobalt ion implantation. For a cobalt ion extraction we studied to sustain the high temperature($648^{°}C$) for metal ions vaporization from a cobalt chloride powder by using an alumina crucible in the ion source. The temperature condition of the crucible was satisfied with the plasma generation at the arc current of 120V and EHC power of 250W. The extracted beam current of $Co^+$ ions was dependent on the arc current in the plasma. The maximum beam current was $100μA$ at 0.18A of the arc current. The 3 peak currents of the extracted ions such as $Co^+$, $CoCl^+$ and $Cl^+$ were obtained by adjusting a mass analyzing magnet and the $Co^+$ ion beam peak current fraction as around 70% in the sum of the peak currents. The fluence of the implanted cobalt ions at the $10μA$ of the beam current and 90 minutes of the implantation time into an aluminum sample as measured around $1.74{×}10^{17}#/cm^2$ by a quantitative analysis method of RBS (Rutherford Backscattering Spectrometry).